Structures of the fibrous dolomite crystals in methane seep carbonates from Marmorito, northwest Italy - Yang Lu; Carsten Paulmann; Boriana Mihailova; Thomas Malcherek; Daniel Birgel; Matthias López Correa; Zhiyong Lin; Liuyi Lu; Yvonne Milker; Jörn Peckmann (PANGAEA, 2023)
Samples were made into 100 μm rock slices. Points of interest were aligned to the beam and measured with φ scans +/- 25° at χ = 0°, 30°, 60° and 90°, respectively. Stepsize of φ was 1° and exposure time was 10 seconds. Results were converted to powder diffraction diagrams by the CrysAlisPro software package.
In: Lu, Y et al. (2023): MgCO? contents, structure, and carbon and oxygen isotope compositions of fibrous crystals in a Miocene methane seep carbonate [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963595